The human side of innovation management: Bridging the divide between the fields of innovation management and organizational behavior - Matthias Weiss; Markus Baer; Martin Hoegl (Journal of Product Innovation Management, 2022)
The human side of innovation management focuses on the people that are carrying out innovative endeavors in organizations. It marks the intersection between research on innovation management and organizational behavior. However, these two research areas are not well integrated in the current literature, despite the many promises such an integration holds to address the challenges innovative organizations, as well as their employees, are facing in general and in times of uncertainty and transformation in particular. This editorial provides an overview of the special issue and illustrates the divide between research on innovation management and organizational behavior. Applying bibliometric analysis, we point to the need to bridge research in these two areas. Aimed to act as a catalyst for such bridging efforts, this special issue on the human side of innovation brought together research based on different theoretical perspectives and diverse methodological approaches. In this regard, the analysis of the intellectual structure of the special issue articles, reported in this editorial, provides evidence the effectiveness of the intended catalysis.
Keywords: 650; bibliometrics; citation analysis; creativity; innovation management; organizational behavior